Presentación atípica de celulitis orbitaria en recién nacido - Jenny Planchet; Koana Rojas; Pedro Blanco (Revista Digital de Postgrado, 2021)
Orbital cellulitis represents a frequent cause of inflammation of the orbit, constituting a medical emergency that requires multidisciplinary management. We present a case of a newborn with clinic of volume increase in right bipalpebral region and fever of 24 hours of evolution. Physical examination reveals proptosis of right eye, increase of bipalpebral volume that prevents the opening of the eyeball in its entirety with signs of flushing and purulent eyelid margin secretion. Laboratories report leukocytosis and reactive thrombosis; orbital tomography scan shows right periorbital swelling and edema, diffuse increase of extra and intraconal post-septal fat density, suggestive findings of right orbital cellulitis, covered with vancomycin and cefotaxime; subsequently requires abscess drainage where Staphylococcus aureus methycilin- resistant is isolated. Being an unusual pathology in this age group, the publication of this case is recommended. Key word: Celullitis, orbital abcess, new born